1984
DOI: 10.1007/bf00214251
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of loading-induced changes in collagen-fibril populations in young tendons

Abstract: This study was designed to gain more detailed morphological information on skeletal tendons in the course of adaptation to physical loading. The effect on collagen fibrils was investigated in 6-week-old mice by means of electron microscopy. Physical loading was performed on a treadmill 5 days a week for 1, 3, 5, 7 and 10 weeks. Morphometric analysis of collagen fibrils revealed the mean diameter, the diameter distribution, the number and the cross-sectional area. The principal observations included: 1. After o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 34 publications
6
64
1
Order By: Relevance
“…Considering these ®ndings, it seems that the dierence in MTC compliance between LDR and CON might be attributable to the dierence in muscle ®bre composition, which has been considered to be inuenced largely by genetic factors (Komi et al 1977). In addition to the above quoted training studies, however, some researchers have shown that physical loading on the tendon increases the number, diameter and degree of alignment of the constituent collagen ®bres (Michna 1984;Nakagawa et al 1988;Vilarta and Vidal 1989). Moreover, Nakagawa et al (1989) have observed that the cross-sectional area of the Achilles tendon in LDR was signi®cantly greater compared to that in untrained individuals.…”
Section: Discussionmentioning
confidence: 91%
“…Considering these ®ndings, it seems that the dierence in MTC compliance between LDR and CON might be attributable to the dierence in muscle ®bre composition, which has been considered to be inuenced largely by genetic factors (Komi et al 1977). In addition to the above quoted training studies, however, some researchers have shown that physical loading on the tendon increases the number, diameter and degree of alignment of the constituent collagen ®bres (Michna 1984;Nakagawa et al 1988;Vilarta and Vidal 1989). Moreover, Nakagawa et al (1989) have observed that the cross-sectional area of the Achilles tendon in LDR was signi®cantly greater compared to that in untrained individuals.…”
Section: Discussionmentioning
confidence: 91%
“…Tendon strength and mechanical properties are affected by tendon dry mass, collagen content, and cross-linking [13][14][15][16]. Although the impact of exercise training on collagen content and cross-linking in human tendon tissue is unknown, animal data has shown increased collagen content with chronic training and biomechanical studies have revealed that tendon stiffness increases in tendons after long exercise [17,18]. This is the first study that has investigated the elasticity features of the patellar tendon in addition to the quadriceps tendon in athletes and healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, patellar tendons, when surgically transplanted to replace torn anterior cruciate ligaments, gradually assume the structural, biochemical and functional characteristics of ligaments in response to their new loading conditions as ligaments [18]. These and other findings [4,[19][20][21][22] indicate that repaired tendons may heal faster when subjected to functional loads. Therefore, earlier in our studies, we implemented minimal (short duration) cast immobilization to facilitate functional loading and rapid repair of experimentally tenotomized rabbit Achilles tendons.…”
Section: Effect Of Functional Loadingmentioning
confidence: 99%